Analysis of Implementation of Academic Supervision of School Supervisors in Efforts to Improve Teacher Professionalism - Merdekawaty, Anna; Andriani, Nining (International Research-Based Education Journal, 2023)
Academic Supervision activities are activities planned to assist teachers in the learning process as an effort to improve teacher competence in order to improve student learning outcomes. This study aims to find out about the implementation of school supervisor supervision in increasing teacher professionalism and improving the quality of education at SMP Negeri 1 Unter Iwes Sumbawa. The approach in this study is a qualitative approach and data obtained by observation, documentation and interviews. The results of the study show (1) the supervision carried out by applying the official, partnership and familial approach, as well as the techniques developed by supervisors in carrying out academic supervision are quite varied; (2) the constraints of supervisors/supervisors in carrying out academic supervision are the large number of teachers, but limited time; (3) the implementation of general academic supervision is quite good, and is able to carry out its duties and functions properly; (4) the aspects that are the target of supervision by school supervisors/supervisors are still limited, not all aspects of academic supervision have been carried out; (5) the frequency of visits by school supervisors/supervisors in conducting academic supervision is considered insufficient because it is not evenly distributed; teachers receive class visits by supervisors; and (6) the efforts made by supervisors/supervisors in carrying out academic supervision, have not been optimal in providing guidance to teachers at SMP Negeri 1 Unter Iwes Sumbawa.